PERAN GREENPEACE DALAM MENANGGULANGI KEPUNAHAN ORANGUTAN DI INDONESIA TAHUN 2009-2015 - Wildan Al Farouq (HI 16 UMY 117, 2016)
*117 This article contains about the pace of the threat extinction of endangered species orangutan in Indonesia. this is caused by the widespread clearing of forest land as native Orangutans habitatDeforestation is carried out by multinational companies ( MNCs) such as Sinar Mas Group, Nestle, IOI, KLK which change the function of forests into oil palm agriculture, industrial land, and development. With deforestation of this forest, Orangutans habitat become desperate and deliver orangutan to the extinction. Of these cases, Greenpeace as an NGO engaged in the environment did not only silent. Greenpeace researched the case and launched a campaign actions on the state of Orangutans in Indonesia, beside that Greenpeace also put pressure on the government in law enforcement to tackle the extinction of these primates.